PENGARUH PENGUMUMAN DIVIDEND TERHADAP PERUBAHAN HARGA SAHAM DAN JUMLAH LEMBAR SAHAM TERJUAL DI - Nainggolan, Ringkot P; Samosir, Maralus (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2022)
Dividend is one of the returns factors desired by investors from investing their capital so that the announcement of the dividend is often an interesting phenomenon for investors. This study uses 29 companies that are member of the LQ45 stock group. The purpose of this study was to analyze the effect of dividend announcement on the price changes and the number of the shares sold on the Indonesia Stock Exchange (IDX) for 3 consecutive years, namely 2016-2018. This study uses event studies by using data 15 days before and 15 days after the dividend announcement. Based on the result of the study it can be concluded that the announcement of the dividends gives a significant difference to the share prices of all LQ45 companies.